Muslim And Hindu Women’s Inheritance Rights in Bangladesh: An Empirical Study - Asrafuzzaman, A B M; Sultana, Shirin; Hasan Sawon, Rubiaat (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to examine the status of Muslim and Hindu women’s inheritance issues in Bangladesh through empirical research. The empirical study aims to investigate the perceptions of ordinary people (both men and women) regarding inheritance issues, in conjunction with expert observations, and to assess the impact of such perceptions on women’s empowerment and the country’s development agendas. Based on the empirical findings, the study suggests some workable solutions that the Government may consider to ensure gender equality and fulfill its commitments under the SDGs.